Kandungan Gizi Mikro (Besi, Seng), Nitrit dan Formalin pada Daging Sapi dari Pasar Tradisional dan Swalayan - Alegantina, Sukmayati; Isnawati, Ani; Winarsih, Winarsih; Ernawati, Fitrah; Imanningsih, Nelis; Setyorini, Herni Asih (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Beef is a nutritious food to consume due to its nutrient content that needed by human body. The demand for beef increases in certain times, such as in religion event or in the holiday. Special treatment is needed for the slaughter time to ready to consume beef, such as freezing or refrigerating. This research aimed to identify the quality of fresh beef as well as frozen beef in the traditional market and frozen beef in supermarket regarding its content of micronutrient (iron and zinc), preservatives (nitrate), and another dangerous additional food (formaldehyde) in cub roll, upper thighs, and lower thighs of beef. This was a cross-sectional and laboratory observational designed research. The result showed that iron, zinc, and nitrite concentration on fresh beef and frozen beef in traditional market and supermarket on any side of the beef sample was not significantly different (p>0.05). Nitrite concentration was within the permitted level. All beef samples also had not contain formaldehyde.